Анализ условий использования бортового генератора в качестве стартера газотурбинного двигателя - Милых, Владимир Иванович; Павленко, Татьяна Павловна (НТУ "ХПИ", 2010)
The question of the use of side turbogenerator, working from a gas-turbine engine and as a starter of the same engine, is examined. There is a simple and at the same time effective method of estimation of compatibility of parameters of this engine and starter. The method is directed on the exposure of expedience of development of the starter system of generators work in every case.
Analysis of terms of the use of side generator as a starter to gas-turbine engine
Keywords: ротор; механический момент инерции; частота вращения; статор; обмотка; поток магнитный; нагрузка